Michael Fordham : innovations in analytical psychology - Astor, James, 1945- (Makers of modern psychotherapy., 1995)
"Michael Fordham's immense contribution to analytical psychology has been marked by its combination of practical and theoretical genius. Before his retirement he ran a full clinical practice while concurrently developing the Society of Analytical Psychology and its child and adult training co-editing the Collected Works of C.G. Jung and editing the Journal of Analytical Psychology for fifteen years. In his published work there has emerged a consistent and original contribution to Jungian thought, particularly in relation to the processes of individuation in childhood, and the links between analytical psychology and the work of the Klemians." "In this important addition to the series of Modern Makers Psycho-therapy, James Astor takes a critical and informed look at Fordham's work and ideas. Using clinical examples to illustrate Fordham's theories the author evaluates key developments in his work, and shows the fundamental ways in which it develops Jung's theory in theory and practice."--Jacket